Arbuscular and Ectomycorrhizal Fungi Associated with the Invasive Brazilian Pepper Tree (Schinus terebinthifolius) and Two Native Plants in South Florida - Dawkins, Karim; Esiobu, Nwadiuto (Frontiers in Microbiology, 2017)
The potential role of soil fungi in the invasion of the Brazilian pepper tree (Schinus terebinthifolius - BP) in Florida is not known; although the low biotic resistance of Florida soils is often invoked to explain the prevalence of many invasive species. To gain an initial insight into BP’s mycorrhizal associations, this study examined the rhizobiome of BP and two native plants (Hamelia patens and Bidens alba) across six locations. Arbuscular mycorrhizal fungi (AMF) associated with the roots of the target plants and bulk soil was characterized by spore morphotyping. Sequence analysis of metagenomic DNA from lateral roots / rhizosphere of BP (n=52) and a native shrub H. patens (n=37) on the same parcel yielded other fungal associates. Overall, the total population of AMF associated with BP was about two folds greater than that of the two native plants (p = 0.0001) growing on the same site. The dominant AMF under Schinus were members of the common Glomus and Rhizophagus spp. By contrast, the most prevalent AMF in the bulk soil and rhizosphere of the two Florida native plants, Acaulospora spp (29%) was sharply diminished (9%) under BP rhizosphere. Analysis of the ITS2 sequences also showed that Schinus rhizosphere had a high relative abundance of ectomycorrhizal fungi (76.5%) compared to the native H. patens (2.6%), with the species Lactifluus hygrophoroides (Basidiomycota) being the most prevalent at 61.5% (p <0.05). Unlike the native plants where pathogenic fungi like Phyllosticta sp., Phoma sp. and Neofusicoccum andium were present (8.1% for H. patens), only one potentially pathogenic fungal taxon was detected (3.9%) under BP. The striking disparity in the relative abundance of AMF and other fungal types between BP and the native species is quite significant. Fungal symbionts could aide plant invasion via resource-use efficiency and other poorly defined mechanisms of protection from pathogens in their invaded range. This report exposes a potentially significant but previously unappreciated fungal dimension of a complex invasion system and underscores the need to characterize these fungal symbionts, their role and mode of action during invasion; with the goal of devising measures for invasion control and ecological restoration.